Angioinvasive mucormycosis and paradoxical stroke: a case report. Issue 4 (July 2016) - Mititelu, Roxana; Bourassa-Blanchette, Samuel; Sharma, Karan; Roth, Virginia
Abstract : Introduction: Rhizopus typically results in acute, aggressive and angioinvasive infection, particularly in immunosuppressed individuals. Risk factors include immunosuppression in haematologic malignancy, uncontrolled hyperglycemia, iron overload states, and older chelator agents such as deferoxamine. Case Presentation: We describe a case of a 33-year-old female with transfusion-dependent beta thalassemia who was started on intravenous deferiprone therapy and subsequently presented with a retropharyngeal abscess. Despite intravenous broad spectrum antibiotics, she continued to deteriorate and developed aphasia. A CT scan of her head showed multiple hypodensities. Blood cultures grew Rhizopus species and a subsequent transesophageal echocardiogram showed a mass in the right atrium with a patent foramen ovale. Conclusion: Although deferiprone, a newer iron chelator agent, has antifungal properties in vivo, this case illustrates that angioinvasive Rhizopus infections can occur in patients treated with deferiprone.